Influence of Immobilization Strategies on the Antibacterial Properties of Antimicrobial Peptide-Chitosan Coatings - Barbosa, M (2023)
It is key to fight bacterial adhesion to prevent biofilm establishment on biomaterials. Surface immobilization of antimicrobial peptides (AMP) is a promising strategy to avoid bacterial colonization. This work aimed to investigate whether the direct surface immobilization of Dhvar5, an AMP with head-to-tail amphipathicity, would improve the antimicrobial activity of chitosan ultrathin coatings. The peptide was grafted by copper-catalyzed azide-alkyne cycloaddition (CuAAC) chemistry by either its C- or N- terminus to assess the influence of peptide orientation on surface properties and antimicrobial activity. These features were compared with those of coatings fabricated using previously described Dhvar5-chitosan conjugates (immobilized in bulk). The peptide was chemoselectively immobilized onto the coating by both termini. Moreover, the covalent immobilization of Dhvar5 by either terminus enhanced the antimicrobial effect of the chitosan coating by decreasing colonization by both Gram-positive (Staphylococcus aureus, Staphylococcus epidermidis) and Gram-negative (Escherichia coli, Pseudomonas aeruginosa) bacteria. Relevantly, the antimicrobial performance of the surface on Gram-positive bacteria depended on how Dhvar5-chitosan coatings were produced. An antiadhesive effect was observed when the peptide was grafted onto prefabricated chitosan coatings (film), and a bactericidal effect was exhibited when coatings were prepared from Dhvar5-chitosan conjugates (bulk). This antiadhesive effect was not due to changes in surface wettability or protein adsorption but rather depended on variations in peptide concentration, exposure, and surface roughness. Results reported in this study show that the antibacterial potency and effect of immobilized AMP vary greatly with the immobilization procedure. Overall, independently of the fabrication protocol and mechanism of action, Dhvar5-chitosan coatings are a promising strategy for the development of antimicrobial medical devices, either as an antiadhesive or contact-killing surface.